Parietal wall post-traumatic hernia with multiple injuries: A rare case report - Apte, Ashwin; Dausage, Chirag Shanti (Indian Journal of Child Health, 2017)
Traumatic abdominal wall hernia (TAWH) is a rare entity. Most of the cases occur in children, following an injury from the bicycle handlebar. In adults, it usually results from road traffic accidents (RTA). The diagnosis may often be established with physical examination alone. Conventional radiology, computerized tomography, and ultrasound have also proven useful. Due to the high incidence of other associated intra-abdominal injuries, early exploration and repair through a midline incision are advocated. Adequate debridement and solid repair of fascial planes with non-absorbable sutures are required to prevent recurrence. We present a case of TAWH following RTA managed by delayed repair without mesh.